The repeal of the glass-steagall act and the Federal Reserve's extraordinary intervention during the global financial crisis - Yeva Nersisyan (Levy Economics Institute of Bard College, 2015)
Before the global financial crisis, the assistance of a lender of last resort was traditionally thought to be limited to commercial banks. During the crisis, however, the Federal Reserve created a number of facilities to support brokers and dealers, money market mutual funds, the commercial paper market, the mortgage-backed securities market, the triparty repo market, et cetera. In this paper, we argue that the elimination of specialized banking through the eventual repeal of the Glass-Steagall Act (GSA) has played an important role in the leakage of the public subsidy intended for commercial banks to nonbank financial institutions. In a specialized financial system, which the GSA had helped create, the use of the lender-of-last-resort safety net could be more comfortably limited to commercial banks. However, the elimination of GSA restrictions on bank-permissible activities has contributed to the rise of a financial system where the lines between regulated and protected banks and the so-called shadow banking system have become blurred. The existence of the shadow banking universe, which is directly or indirectly guaranteed by banks, has made it practically impossible to confine the safety to the regulated banking system. In this context, reforming the lender-of-last-resort institution requires fundamental changes within the financial system itself.
Keywords: B50; E50; E58; G10; G18; 330; Banks; Central Banking; Deregulation; Federal Reserve; Financial Crises; Glass-Steagall Act; Lender of Last Resort; Minsky; Regulation; Securitization; Shadow Banking